Pengaruh Uang Saku, Teman Sebaya, Lingkungan Sekitar Terhadap Pengendalian Diri Mahasiswa Dalam Pengelolaan Keuangan Di Era Covid-19 - Lesminda, Ester; Rochmawati, Rochmawati (Jurnal Pendidikan Akuntansi (JPAK), 2021)
Student self-control when managing finances today is dependent on pocket money, peers, and the surrounding environment. In terms of managing finances, students need to control themselves with three factors, namely; Pocket money, Peers, and The Neighborhood. This study aims to find out the influence of pocket money, peers, and the surrounding environment as variable moderators. This research uses quantitative research. Data collection using questionnaires with a population of 100 undergraduate students from various universities in Indonesia. Sample techniques that will be used Simple Random Sampling Techniques, with the criteria used are undergraduate students who are still active in lectures. The data analysis used is multiple linear analysis. The results prove 1) pocket money significantly negatively affects students' self-control in financial management 2) Peers significantly positively affect financial management 3) The surrounding environment has a significant positive influence on students' self-control. The results showed that pocket money, peers, and the surrounding environment simultaneously have a significant influence on students' self-control in financial management in the era of covid-19.